PERAN KEPEMIMPINAN KEPALA PERPUSTAKAAN UNIVERSITAS TANJUNGPURA DALAM MENINGKATKAN KINERJA PEGAWAI - Ambarini, Intania Citra; Priyadi, Antonius Totok (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study discusses the leadership of the library chief on the performance of employees at the University Library Tanjungpura. The purpose of this study is to knowthe role of the head of library leadership in improving the performance of employees, constraints the head of the library in improving the performance of employees, as well as efforts made the head of the library as pemipin in the library of Tanjungpura University. In this study, the authors retrieve data using qualitative and descriptive methods. Data collection is done by observation to the field. interviews, and documentation.The results of this research are 1) The role of leadership is very important in improving the performance of employees 2) Head of Tanjungpura University library into the category of Democratic leadership type and can change the discipline of employees better.Â Keywords: Head of Library, Leadership, Peagawai Performance, High Pergurun LibraryÂ